Marketing de Relacionamento através da Internet: uma análise em empresas cearenses de TI - Moreira, Francisca Fernanda Rocha (2009)
The use of the Internet in business has been increasingly discussed by organizations because of its low cost, speed of communication and interactivity. Therefore, companies seek to develop a relationship with their customers in order to gain satisfaction, trust and commitment. This fact impelled the present study to try to detect if the IT (Information Technology) companies use the Internet as a tool of customer relationship and how it is done. Despite being the creator and disseminator of digital tools in organizations in general, it is believed that its companies still use the Internet in the relationship with their customers in an incipient way. Thus, the level of web usage by the companies is discussed, through the model proposed by Bauer et al. (2002), and how this may influence satisfaction, trust and commitment of the customers of these companies. This discussion is based on a case study of an IT company with expressiveness in the local market and a questionnaire applied to the customers of this company, apart from its application to the literature discussed.